2019
DOI: 10.3390/cancers11111727
|View full text |Cite
|
Sign up to set email alerts
|

AXL Receptor Tyrosine Kinase as a Therapeutic Target in Hematological Malignancies: Focus on Multiple Myeloma

Abstract: AXL belongs to the TAM (TYRO3, AXL, and MERTK) receptor family, a unique subfamily of the receptor tyrosine kinases. Their common ligand is growth arrest-specific protein 6 (GAS6). The GAS6/TAM signaling pathway regulates many important cell processes and plays an essential role in immunity, hemostasis, and erythropoiesis. In cancer, AXL overexpression and activation has been associated with cell proliferation, chemotherapy resistance, tumor angiogenesis, invasion, and metastasis; and has been correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 92 publications
1
19
0
Order By: Relevance
“…(Scheme 1) The N-Boc protecting group was transformed to a trifluoroacetyl group (4) to secure the next transformation. Various phenyl or aromatic groups (5) were introduced by palladium-catalyzed cross coupling conditions with R 1 -boronic acids. Treatment of compound 5 with aromatic amines yielded 2,2,2-trifluoro-1-(4-((5-phenyl-2-(phenylamino)pyrimidin-4-yl)amino)piperi-din-1-yl) ethan-1-one (6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Scheme 1) The N-Boc protecting group was transformed to a trifluoroacetyl group (4) to secure the next transformation. Various phenyl or aromatic groups (5) were introduced by palladium-catalyzed cross coupling conditions with R 1 -boronic acids. Treatment of compound 5 with aromatic amines yielded 2,2,2-trifluoro-1-(4-((5-phenyl-2-(phenylamino)pyrimidin-4-yl)amino)piperi-din-1-yl) ethan-1-one (6).…”
Section: Resultsmentioning
confidence: 99%
“…The water layer was extracted with EtOAc twice, and the organic layers were dried over Na 2 SO 4 and concentrated under reduced pressure. 1-(4-((2-Chloro-5-phenylpyrimidin-4-yl)amino)piperidin-1-yl)-2,2,2-trifluoroethan-1-one (5). 1-(4-((5-Bromo-2-chloropyrimidin-4-yl)amino)piperidin-1-yl)-2,2,2-trifluoroethan-1-one (200 mg, 0.51 mmol, 1.0 eqiv) was dissolved in DMF (2 mL) then phenylboronic acid (94 mg, 0.77 mmol, 1.5 eqiv), Pd(dppf) 2 Cl 2 (19 mg, 0.02 mmol, 0.05 eqiv), K 2 CO 3 (164 mg, 1.55 mmol, 3.0 eqiv) were added and stirred at 80 C for 12 h. After the completion of the reaction, the reaction mixture was extracted twice, and the combined organic extracts were dried (Na 2 SO Induced Fit Docking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies revealed that Axl is a key molecule in hematological malignancies including multiple myeloma 7 and metastatic breast cancer 8 . The combination of a pan-TAM kinase inhibitor, BMS-777607, with anti-PD1 resulted in a better anti-tumour effect than each monotherapy alone in a mouse model 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al reviewed the role of AXL , a member of the TYRO3/AXL/MERTK receptor tyrosine kinase family, in solid cancers and hematological malignancies [ 4 ]. AXL is involved in the regulation of cell survival, proliferation, angiogenesis, and immune modulation.…”
mentioning
confidence: 99%